(untitled) (Journal of Economic Research & Business Administration, 2015)
The theoretical and practical questions on necessity of management of credit risk for banks are considered. The interrelation of activity of commercial banks directly with credit risk is opened. The complexity of management of credit risk is proved, the conclusions on quality of a loan portofolio are made in view of crisis in bank sector of Kazakhstan.